ANALISIS KEBIJAKAN KURIKULUM SISTEM PENDIDIKAN NASIONAL ( SPN)-21: PELUANG DAN TANTANGANNYA BAGI PENDIDIKAN ISLAM DI BRUNEI DARUSSALAM - Susiba, Susiba; Hairunnas, Hairunnas; Helmiati , Helmiati (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2022)
The SPN-21 curriculum policy is the latest curriculum policy in the country of Brunei, which was launched in order to create people who are faithful, devoted, have noble character and master technology. However, if a policy is not properly prepared, it will experience weaknesses in many aspects. This paper aims to examine the weaknesses in the implementation of the SPN-21 curriculum and how they impact Islamic education in Brunei. The type of research used is a literature review. Based on the results of the literature review, it is known that there has been no careful preparation from the Brunei government in the realization of the SPN-21 curriculum, including the need for proficiency in English in order to master technology. Although persistent efforts have been made in mastering English. In addition, it is difficult for Islamic educational institutions to adapt to the SPN-21 curriculum policy, because it cannot be denied that Islamic educational institutions focus more on teaching religious subjects, but are weak in technology. Although there are already schools that are trying to integrate religion with science, such as Technical College, but not much.